Construyamos el territorio departamental entre todos: Nuevos enfoques de planificación participativa en Maldonado, Uruguay (ARQUISUR Revista, 2010)
This article describes the implementation of a participatory land planning in the Department of Maldonado, its micro-regions and towns, in the context of the Law of Land Management and Sustainable Development aproved in 2008. The initiative of the Local Government (IMMa), is based on the advice of the Faculty of Architecture-UdelaR for implementing participatory process, which is embodied in the formation of so-called "Land Workshops", at multi-stakeholder participation level. These worktables are wide-ranging appeal, with the involvement of organizations and actors working together in an interdisciplinary way and with the technical team of the Faculty of Architecture and IMMa, establishing a strategic land planning system, open and participatory. In practice, they become spaces for interaction between governance and social and private actors, in a land subject to multiple stresses and dynamics of migration as it is Maldonado, with deep economic and social disparities that create a heterogeneous landscape.The links created with the Community began in 2006, and remains continuously until present, with high social impact, constantly verifying its feasibility.
Keywords: cultural landscapes; heritage; human and local development; land management; land planning; planning participative process; tourism